An empirical investigation on the antecedents of consumers' cognitions of and attitudes towards digital signage advertising. Issue 1 (2nd January 2019) - Lee, Heejun; Cho, Chang-Hoan
ABSTRACT: This paper investigates the antecedent factors of consumers' perceived values and attitudes towards digital signage advertising in a structural model. The results of this study revealed that four key antecedents (i.e. informativeness, involvement, entertainment and targeting) affect consumers' attention to digital signage advertising and perception of advertising values. This study shows that attitudes towards digital signage and perceived interactivity with it also affect consumers' attitudes towards digital signage advertising. This, in turn, influences positive attitudes towards a brand and higher purchase intentions.